Recent Advances in Child and Adolescent Psychiatry - Chiappedi, Matteo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Psychiatric disorders in children and adolescents are relevant both in terms of their prevalence (they are roughly estimated to affect about 20% of school-aged children and adolescents) and of their impact on the quality of life of the child/adolescent and their family, but also on the society as a whole. Disorders affecting children and adolescents are increasingly seen as having highly specific features, and, therefore, require an equally specific approach despite the coexisting need to integrate contributions from other professions (e.g., pediatricians, psychiatrists, psychologists, and therapists of different sorts). However, the available data are still insufficient, especially for treatment options and too often therapeutic choices are still made based on studies conducted in adults. Even more important, the existence itself of some disorders is questioned especially outside the scientific field (e.g., ADHD). This Special Issue provided cutting edge data on different aspects of child and adolescent psychiatry, including etiopatogenesis, clinical characteristics and diagnosis, medical and neurological comorbidities (and psychiatric comorbidities of medical and neurological disorders), impact on patients/families/society (including school and other social groups), prognosis, and treatment options of the different disorders.